OUT-fit Clothing / Muhammad Amirul Taufiq Ismail ... [et al.] - Ismail, Muhammad Amirul Taufiq; Mohd Sukri, Muhammad Firdaus; Abdullah, Andy Roy; Johari, Nur Hidayah (2021)
To begin with, most of every individual’s lifestyles today are heavily influenced with fashion. This include today’s trend where the younger generation are more interested in wearing streetwear outfits in their everyday occasions. Streetwear is no longer a strange style, but rather a normalcy in today’s fashion industry where it is a style of casual clothing that may combine numerous elements such as sportswear,new wave, heavy metal, punk, Los Angeles surf skate culture, and Japanese street fashion. Originally, streetwear style came from New York hip hop fashion and increasingly became gobal in the 1990 until today. This trend is usually followed by youngsters that are in high school and even young adults that are pursuing for their diploma and degree, including young adults who are fresh graduates. To conclude, most individuals that prefer wearing streetwear outfits are in the range age of 16 to 28 because they are more concerned of how they represent themselves in terms of radiating their personality through fashion. However, we notice that most manufacturers or business that strives in clothing business are quite expensive for younger generations since majority of them are students, and not workers. According to our surveys on our competitors, we notice that even one t-shirt can cost up to RM 100 based on the materials and designs. Although good qualities are much favoured almost by every customers, we would like to provide an option of a much affordable outfits that still have good qualities in terms of materials and designs. Therefore, our business named OUT-fit that will be handled by 4 partners will start up on our business by releasing t-shirts that will focus more on our qualities. Ideally, the material of our t- shirts will be made up of 60% cotton which is soft, absorbent, breathable and has cooling effect. The designs will be simple and yet trendy, as the famous saying goes, "less is more”. Our customers will be provided with sundry of designs to choose from since we will be releasing a lot of designs suiting each individual’s interest time by time. As our business grew even larger by years, we will surely add more option of our streetwear outfits such as jeans, caps, or sneakers since streetwear style can be included in almost any outfits. 2